Edukasi dan Pelatihan Pembuatan Balsem Jahe Merah (Zingiberis officinale) Sebagai Obat Rematik Pada Ibu-Ibu Desa Tengah, Deli Serdang, Sumatera Utara - Masniah, Masniah; Hilda, Hilda; Yusnita, Henny (Shihatuna : Jurnal Pengabdian Kesehatan Masyarakat, 2025)
Rheumatic diseases are among the leading causes of activitylimitations, particularly affecting elderly women. This studyaims to provide education and training to the community inDesa Tengah, Kecamatan Pancurbatu, on the treatment ofrheumatism using red ginger (Zingiberis officinale) balm. Theapproach used involved educational outreach and hands-ontraining, starting with a pre-test questionnaire to assess thecommunity’s baseline knowledge, followed by a lecture onrheumatism and the medicinal benefits of red ginger.Afterward, a demonstration on how to make red ginger balmwas conducted, with materials provided so participants couldpractice making the balm at home. The results of the activityshowed a significant increase in community knowledge, with80% of participants demonstrating good knowledge after thetraining, up from 16.67% prior to the education. Furthermore,the community successfully learned to create red ginger balm,which proved effective in alleviating rheumatic symptoms.This activity is expected to promote the use of medicinalplants, particularly red ginger, as an affordable and safealternative treatment for rheumatism. The findings suggestthat community education and empowerment can reducedependence on chemical medicines and improve the qualityof life for rheumatic patients.